Unity and harmony in Malaysia: problems and challenges - Abdullah @ Chuah Hock Leng, Osman (British Journals, 2012)
Malaysia is very much a diversified nation with a population of about 28 millions from different ethnic groups and with a variety of religions. Despite having no significant nor violent racial and religious conflict since 1969, there have been signs of emerging ethnic tension and sensitive issues every now and then in the nation. This study demonstrates how the political, economic, social and educational issues are contentious to unite or divide the people. The main ethnic group in Malaysia consists of the Malays who constitute the majority of more than half of the population, who are mostly Muslims. This is followed by the minority groups of Chinese and Indians. Islam is the official religion in Malaysia and of the Malays while there are other religious faiths of Buddhism, Taoism, Christianity and Hinduism. In the states of Sabah and Sarawak, there are natives of smaller ethic groups such as Kadazan, Dayak, Iban and others. The various ethnic groups celebrate their festivals throughout the year and their customs and value systems too are different from one another. The Malays and the natives are known as bumiputra whereas the Chinese and Indians are non-bumiputra. This research seeks to study the problems and challenges on the subject of unity and harmony in Malaysia with regard to the diversity of languages, religions, cultures and how the dimensions of politics, economics, education and social affect them.